CURPH Interview 130 with a 1956 Hungarian Refugee: 48 Years Old, Female, Typographer, housewife - Columbia University School of International Affairs
Transcript of an interview conducted as part of the Columbia University Research Project on Hungary (CURPH) in the wake of the 1956 Hungarian Revolution. Place of Interview: New York (N.Y.) Interview ID: 130 Interview Type: A Covers topics related to everyday life and politics in Hungary between the end of World War II and the 1956 Hungarian Revolution. The document notes that the interviewee had the following characteristics: Education level: High-school Occupation: Typographer, housewife Religious preference: Roman Catholic Place of residence before emigration: Budapest